Manufacturing-based relatedness, synergy, and coordination - John, Caron H. St.; Harrison, Jeffrey S. (Strategic Management Journal, 1999)
This paper explores the basic question of whether manufacturing-based relatedness between business units within a multibusiness firm serves as a basis for a competitive advantage at the business unit level. We developed a system for describing manufacturing relatedness that combines the study of value chain activities with 4-digit SIC codes, then we assessed presence of manufacturing synergies. We found no evidence that, on average, organizations involved in manufacturing-related businesses are reaping financial benefits from shared resources in manufacturing. However, some firms, through explicit commitment to coordination, do realize performance benefits from such involvement. Copyright © 1999 John Wiley & Sons, Ltd.